2018
DOI: 10.1021/acs.energyfuels.8b00269
|View full text |Cite
|
Sign up to set email alerts
|

Wax Deposition Experiment with Highly Paraffinic Crude Oil in Laminar Single-Phase Flow Unpredictable by Molecular Diffusion Mechanism

Abstract: Wax deposition data for a Brazilian crude oil was investigated using a facility designed to study flow assurance problems related to waxy crude oils. This work reports the preliminary efforts behind validating the pressure drop methods in place for identifying deposition, i.e., isothermal and nonisothermal flows were evaluated, to confirm whether it was possible to differentiate between temperature gradient effects, and wax deposition. Additionally, deposition experiments show a phenomenon that is not commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 42 publications
0
19
0
12
Order By: Relevance
“…However, it was reported recently that models based on the molecular diffusion approach alone may not predict wax deposition accurately. [95] In contrast, wax deposition in the heat-transfer mechanism is based on the liquid-to-solid phase transformation or (partial) freezing process. [33] In this approach, the liquid-deposit interface temperature remains constant throughout the deposition process, which is taken to be the WAT of the liquid phase.…”
Section: Wax Deposition Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reported recently that models based on the molecular diffusion approach alone may not predict wax deposition accurately. [95] In contrast, wax deposition in the heat-transfer mechanism is based on the liquid-to-solid phase transformation or (partial) freezing process. [33] In this approach, the liquid-deposit interface temperature remains constant throughout the deposition process, which is taken to be the WAT of the liquid phase.…”
Section: Wax Deposition Mechanismsmentioning
confidence: 99%
“…However, it was reported recently that models based on the molecular diffusion approach alone may not predict wax deposition accurately. [ 95 ]…”
Section: Properties Of “Waxy” Oils and Prepared Mixturesmentioning
confidence: 99%
“…After that, with the continuous precipitation of wax crystals, the solid particles will be gradually connected to form a spatial network structure, and the crude oil is wrapped in its pores, which results in a deterioration of flows and eventually causes the blockage of the pipeline. It is concluded that the wax deposition process is influenced by many factors, such as crude oil composition, pipe wall material, temperature, , flow velocity, and flow pattern. , For the wax deposition mechanism, the classical theories include molecular diffusion, , shear dispersion, , Brownian motion, , and gravity deposition. , Recently, with the further development of the wax-deposited research, the mechanisms of shear stripping, gelation (emulsified nucleation) and aging was proposed. , Many scholars have performed research regarding those mechanisms. Hoffmann et al and Mehrotra et al found that the carbon number distribution on the surface of wax deposition layer is closer to that of the flowing oil when the flow rate is low and the water content is high.…”
Section: Introductionmentioning
confidence: 99%
“…For this, many scholars have conducted numerous studies on wax deposition in the multiphase pipelines, and they have a relatively comprehensive understanding of its influencing factors and deposition characteristics. However, with the deepening of the research, the wax deposition mechanism is still needed to be refreshed and improved. ,, Based on recent studies on wax deposition and some classic literatures, this paper summarized the new wax deposition mechanisms proposed by researchers in recent years and several typical experimental devices for studying wax deposition, and the wax deposition characteristics and prediction models in single- and two-phase flow systems and the wax–hydrate coupling deposition in oil–gas–water flow systems have been determined, to provide reference for researchers engaged in single-phase and multiphase flow assurance.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have conducted a lot of study on wax deposition of oil pipelines. It has been acknowledged that molecular diffusion, shear dispersion, gravity settlement and Brownian diffusion are three main mechanisms governing the wax deposition process [5][6][7]. Hamouda and Viken (1993), and Brown and Niesen (1993) believed that the effect of shear dispersion on the wax deposition process is not significant [8,9].…”
Section: Introductionmentioning
confidence: 99%